Integration of Electrical Resistivity Tomography and Borehole Data for Mapping Laterite-Bedrock Boundaries in a Nickel Deposit, 'PHO' Block, Southeast Sulawesi - Ipho Amanah Pahlawantika; Y Yatini; Muhammad Arief Wicaksono (Department of Physics, Sebelas Maret University, 2025)
Indonesia has the largest nickel reserves in the world, so proper exploration is crucial to map the potential and utilization of this resource. Exploration of nickel laterite is carried out by mapping the boundaries of the laterite zone and bedrock as a prospect zone for further exploration. One of the methods used is Electrical Resistivity Tomography (ERT) combined with drill data. The principle of the ERT method involves injecting electric current into the ground to measure variations in subsurface resistivity. These variations in resistivity are then used to map the lithological distribution. ERT data, used as the primary data source to obtain an inversion model, is combined with inline borehole data, involving a total of 8 ERT lines and 23 borehole data points. The integration of both ERT and borehole data characterizes zones of nickel laterite and bedrock. Nickel laterite zones consist of saprolite and limonite lithology, and there is a saprock zone as a transition between the nickel laterite zone and the bedrock. Research in the